Effects of phospholipid type and concentration on the emulsion stability and in vitro digestion behaviors of fish oil-loaded emulsions - YIN,Mingyu (2022)
Abstract Phospholipid (PL) have favorable emulsification ability. The simultaneous application of PL and protein is one of the research hotspots. In this work, the impact of egg yolk PL (EPL), soyabean PL (SPL) and their concentrations on the fish oil-loaded PL/gelatin (GTN)-stabilized emulsions were studied. The results suggested that SPL/GTN-stabilized emulsions comprised bimodal of droplets, and monomodal was observed in EPL/GTN, and GTN-stabilized emulsions. The related droplet sizes were as follows: 1.5% EPL/GTN < 1.0% EPL/GTN < 0.5% EPL/GTN < 2.0% GTN < 0.5% SPL/GTN < 1.0% SPL/GTN < 1.5% SPL/GTN.; and (4) Conclusion: The concentration of PL had significant effect on the droplet size and emulsion stability of the emulsions. The 1.0% SPL/GTN-stabilized emulsions demonstrated the optimal stability and droplet size when stored at room temperature for 15 days than emulsion contained PL. The addition of PL inhibited lipid oxidation and increased the rate of fatty acid release in vitro digestion. This work illustrated that PL/GTN-stabilized emulsions could potentially be a targeted delivery medium for nutrients or drugs.